Toxicogenomics of Gold Nanoparticles in a Marine Fish: Linkage to Classical Biomarkers - Teles, Mariana; Reyes-López, Felipe E.; Balasch, Joan C.; Tvarijonaviciute, Asta; Guimarães, Laura; Oliveira, Miguel; Tort, Lluis (Frontiers in Marine Science, 2019)
In the present study, the underlying short-term effects of gold nanoparticles (AuNP, spheres, citrate coated, ~40 nm) on the hepatic function of gilthead sea bream (Sparus aurata) was assessed, using a species-specific enriched oligonucleotide microarray platform (SAQ). Two distinct concentrations of AuNP (0.5 and 50 μg/L) were tested via 24 h waterborne exposure. The transcriptional profile was complemented with outcomes at higher levels of biological organization, including hepatic health indicators and DNA damage indicators. The DNA damaging potential of AuNP was assessed in whole peripheral blood, assessing DNA strand breaks (using the comet assay) and chromosome damage (scoring the erythrocytic nuclear abnormalities, ENA). The overall genetic response showed a differential hepatic transcriptional profile, both in terms of number and intensity, of differentially expressed genes (DEG). Concerning functional pathways affected, the main changes were found for genes encoding proteins involved in the response to xenobiotics, oxidoreductase activity, immunomodulation, DNA repair and programmed cell death types I and II. The hepatic health indicators measured revealed that AuNP can induce liver injury, as demonstrated by the plasma alanine aminotransferase (ALT) and aspartate aminotransferase (AST) significantly increased activities after exposure to the highest AuNP concentration (50 μg/L). Exposure to AuNP also caused DNA strand breaks, however, without causing clastogenesis or aneugenesis, since no ENA were detected. Overall, data show that a short-term exposure to AuNP can modulate gene expression in liver and affects several biochemical/genetic functions in fish.